Hubungan Tingkat Pengetahuan dengan Perilaku Bullying pada Remaja di SMP Santo Louis Palembang - Anastasia Alvareza Ratih Damayanti; Ketut Suryani (Yayasan Literasi Sains Indonesia, 2023)
Bullying has the meaning of bullying or behavior that disturbs people who are considered weaker. This behavior can be said to be repeated negative actions carried out intentionally with the aim of hurting them physically or mentally. This research uses quantitative methods, analytical survey design with a cross sectional approach. The sample consisted of 64 respondents, taken using a purposive sampling technique. Data was collected using a questionnaire, then univariate and bivariate analysis was carried out. Data were analyzed using Kendall Tau b correlation analysis using a significant value of 5%. The results of this univariate study show that the majority of respondents are 13 years old, 38 respondents (59%) are female, 42 respondents (65.6%) have good knowledge, 58 respondents (90%) have good behavior. .6%). The results of the bivariate analysis showed that there was no significant relationship between the level of knowledge and bullying behavior (τ= 0.050; p= 0.681). It is recommended that institutions can prevent and minimize bullying incidents by providing information or counseling so that teenagers have the self-awareness not to carry out bullying behavior.